Relationship of Therapeutic Communication with Inpatient Satisfaction at the Martha Friska Hospital, Pulau Brayan in 2018 - Niasty Lasmy Zaen (Institute of Computer Science (IOCS), 2020)
Communication is an individual effort in maintaining and maintaining individuals to keep interacting with others and is an important component in nursing practice. Communication is an effective tool to influence human behavior, so that communication is developed and maintained continuously. Objectives In Research on Therapeutic Communication Relationships with Inpatient Satisfaction at Martha Friska Hospital, Brayan Island, 2018. This study used a cross-optional research design. The population in this study were all inpatients on the 3rd floor, amounting to 20 nurses, with a total sampling technique, the number of smapel in this study was 20 people. The data analysis technique was performed using univariant and bivariant statistical analysis. The statistical test in this study used the chi square formula (kai squared) to estimate or evaluate the frequency under investigation has a significant relationship or not, with a 95% degree of confidence. Based on the results of the study, there is a significant relationship between therapeutic communication and satisfaction of inpatients at the Martha Friska Hospital, Pulau Brayan in 2018, with a p value = 0.001 (p <0.05). For research sites, therapeutic communication training is one of the efforts that must be continuously carried out in maintaining or even further improving the quality of service to patients or the community.